2010
DOI: 10.1007/s00415-010-5736-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting employment status in multiple sclerosis patients: the utility of the MS functional composite

Abstract: As many as two-thirds of multiple sclerosis (MS) patients are unable to retain employment. Neurological and cognitive status are known to be significant predictors of unemployment, but the relationship between the two is unclear. Furthermore, the association between employment status and depression, anxiety, and personality has not been adequately explored in MS patients. This study examined the demographic, neurological, neuropsychological, and personality factors associated with unemployment in MS. We also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 38 publications
7
75
1
9
Order By: Relevance
“…Those expecting to reduce their job responsibilities perceived themselves as more severely disabled from their MS symptoms and as more constrained by lack of accessible housing. Adults with MS expecting to exit the workforce in 2 to 5 years presented a profile consistent with the literature pertaining to predictors of employment and unemployment (Honarmand, Akbar, Kou, & Feinstein, 2011;Moore et al, 2013;Schiavelin et al, 2013;Smith & Arnett, 2005). They were older and perceived that they were affected more severely by their MS symptoms, particularly as those symptoms affected their mobility, which is consistent with findings that unemployed adults with MS had the highest level of incapacity in comparisons with employed adults with MS (full-time or part-time).…”
Section: Discussionsupporting
confidence: 82%
“…Those expecting to reduce their job responsibilities perceived themselves as more severely disabled from their MS symptoms and as more constrained by lack of accessible housing. Adults with MS expecting to exit the workforce in 2 to 5 years presented a profile consistent with the literature pertaining to predictors of employment and unemployment (Honarmand, Akbar, Kou, & Feinstein, 2011;Moore et al, 2013;Schiavelin et al, 2013;Smith & Arnett, 2005). They were older and perceived that they were affected more severely by their MS symptoms, particularly as those symptoms affected their mobility, which is consistent with findings that unemployed adults with MS had the highest level of incapacity in comparisons with employed adults with MS (full-time or part-time).…”
Section: Discussionsupporting
confidence: 82%
“…Thus, these findings may suggest, in part, alternative explanations for the high jobless rates among Hispanic/Latino adults with MS such as education level, fatigue related to job duties and roles, and overall progression in disability level, particularly in terms of cognitive limitations (Honarmand et al, 2011;Krause, Kern, Horntrich, & Ziemssen, 2013;Moore et al, 2013;Simmons, Tribe, & McDonald, 2010). Others have cited different nonworksite factors as central to leaving the work force such as disincentives in disability benefits programs (Marini, 2003) and more subtle and difficult to verify forms of workplace discrimination (Rumrill et al, 2005).…”
Section: Significant Strengthsmentioning
confidence: 96%
“…[6][7][8][9][10][11] Other MS symptom-related factors have also been found to predict employment status, including fatigue, 10,12 depression, [6][7][8] motor difficulties, 13 and cognitive problems. 14,15 More specifically, regarding cognitive problems, scores on tests of processing speed, verbal fluency, working memory, and long-term memory are typically lower in unemployed versus employed individuals with MS. 8,16,17 With all this said, research on cognition and depression has produced inconsistent findings. Regarding cognition, although most studies have found it to be associated with employment status, some have not.…”
Section: Methodsmentioning
confidence: 99%